2003
DOI: 10.1007/3-540-36483-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Multi-agent Patrolling: An Empirical Analysis of Alternative Architectures

Abstract: Abstract.A group of agents can be used to perform patrolling tasks in a variety of domains ranging from computer network administration to computer wargame simulations. Despite its wide range of potential applications, multiagent architectures for patrolling have not been studied in depth yet. First state of the art approaches used to deal with related problems cannot be easily adapted to the patrolling task specificity. Second, the existing patrollingspecific approaches are still in preliminary stages. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 7 publications
0
135
0
10
Order By: Relevance
“…One of the first works in this field is described in [2] and in more detail in [3], where several architectures of multi-agent patrolling and various evaluation criteria were presented.…”
Section: Pioneer Methodsmentioning
confidence: 99%
“…One of the first works in this field is described in [2] and in more detail in [3], where several architectures of multi-agent patrolling and various evaluation criteria were presented.…”
Section: Pioneer Methodsmentioning
confidence: 99%
“…Pioneer work on this field was presented in [3] and [4], where very simple approaches with reactive and cognitive agents were proposed as well as a first evaluation criterion based on idleness. Following these works, more advanced approaches based on graph theory became also popular like [5] and [6], which use graph partitioning to assign efficient patrol routes to different robots.…”
Section: Related Workmentioning
confidence: 99%
“…Five state-of-the art patrolling algorithms were implemented, namely: Conscientious Reactive (CR) [3], Heuristic Conscientious Reactive (HCR) [4], Heuristic Pathfinder Conscientious Cognitive (HPCC) [4], Cyclic Algorithm for Generic Graphs (CGG) [5] and Generalized MSP Algorithm (MSP) [5]. These algorithms were combined with six different teamsizes: 1, 2, 4, 6, 8 and 12; and three environments with different connectivity properties: low connectivity (A), medium connectivity (B) and high connectivity (C).…”
Section: Preliminariesmentioning
confidence: 99%
“…Informally, a good strategy is one that minimises the time lag between two passages to the same place and for all places. In [12], it was shown that in many applications of the patrolling problem, the territory could be represented by a graph. Given such a graph, the patrolling task refers to continuously visiting all the graph nodes so as to minimise the time lag between two visits.…”
Section: Example Applicationsmentioning
confidence: 99%